Recent advances in the investigation of a slow‐moving landslide in the Three Gorges Reservoir area, China - Shun Wang; Dian‐Qing Li; Wenqi Du (River, 2022)
Abstract Many slow‐moving landslides in the Three Gorges Reservoir (TGR) area exhibit episodic movement patterns in response to variations in the reservoir water level and seasonal rainfall. These landslides are typically characterized by pre‐existing shear zones composed of thick, clay‐rich layers that are sensitive to hydrological forcings. The residual shear strength of these shear zones is believed to control the dynamic movements of these landslides. In this article, we review the recent advances in the investigation of a large slow‐moving landslide, the Huangtupo landslide, in the TGR area. This landslide has been chosen as a benchmark for studying similar landslides in this area. This review focuses mainly on the research carried out by the authors and their collaborators over the last 5 years on topics including the landslide mechanisms and forcings, rheological behaviors and constitutive models of the landslide materials, the numerical simulation of clastic shear‐zone soils, and the effects landslide‐induced tsunamis would have on the ships in the reservoir. In addition, new perspectives and challenges for future research on slow‐moving landslides are provided.